Detection of Trichomonas vaginalis Using the Polymerase Chain Reaction in Pregnant and Non-Pregnant Women. Issue 1 (1994) - Jeremias, J.; Draper, D.; Ziegert, M.; Jones, W.; Inglis, S.; McGregor, J. A.; Witkin, S. S.
Abstract : Objective: Trichomonas vaginalis vaginal infections are often both asymptomatic and difficult to detect by current methods. We evaluated the ability of a newly developed polymerase chain reaction (PCR) assay to identify T. vaginalis in vaginal samples from pregnant and non-pregnant women. Methods: In the 1st study, we compared the prevalence of T. vaginalis detection by PCR and culture using Diamond's medium in 52 women with symptoms of vaginal infection. In the 2nd study, T. vaginalis was detected using PCR and wet mount microscopy in 131 asymptomatic pregnant women. Results: Among the women with symptoms of vaginitis, 7 (13.5%) were PCR-positive for T. vaginalis . Six of the PCR-positive women, but none of the PCR-negative women, were culture-positive for this organism. All but 1 of the women with candidal vaginitis or bacterial vaginosis were PCR-negative for T. vaginalis . Among the asymptomatic pregnant women, all of whom were negative for T. vaginalis by wet mount, l0 (7.6%) were PCR-positive for T. vaginalis . Conclusions: PCR offers a rapid and sensitive alternative to culture and microscopy for the detection of T. vaginalis vaginal infections in both symptomatic and asymptomatic women.